Stable isotope compounds - production, detection, and application - Zachleder, Vilém; Vítová, Milada; Hlavová, Monika; Moudříková, Šárka; Mojzeš, Peter; Heumann, Hermann; Becher, Johannes R; Bišová, Kateřina (Biotechnology advances, 2018)
Stable isotopes are used in wide fields of application from natural tracers in biology, geology and archeology through studies of metabolic fluxes to their application as tracers in quantitative proteomics and structural biology. We review the use of stable isotopes of biogenic elements (H, C, N, O, S, Mg, Se) with the emphasis on hydrogen and its heavy isotope deuterium. We will discuss the limitations of enriching various compounds in stable isotopes when produced in living organisms. Finally, we overview methods for measuring stable isotopes, focusing on methods for detection in single cells in situ and their exploitation in modern biotechnologies.
Keywords: rostliny; Spectrum Analysis, Raman; Sulfur; Chlorophyta; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; Isotopes; deuterium; Algae; biotechnologie; Mass Spectrometry; Plants; Biotechnology; Carbon; Stable isotopes; zvířata; Mammals; racionální návrh léčiv; savci; Magnesium; Raman spectroscopy; Selenium; izotopy; Oxygen; Drug Design; Deuterium; Isotope Labeling; hmotnostní spektrometrie; Nitrogen; Ramanova spektroskopie; izotopové značení; Animals